Dietary kaempferol exerts anti-obesity effects by inducing the browing of white adipocytes via the AMPK/SIRT1/PGC-1α signaling pathway - Changyu Xu; Xiaoxi Zhang; Yihuan Wang; Yan Wang; Yixuan Zhou; Fenfen Li; Xiaoli Hou; Daozong Xia (Current Research in Food Science, 2024)
Browning of white adipose tissue is a novel approach for the management of obesity and obesity-related metabolic disorders. Kaempferol (KPF) is a common dietary nutrient found abundantly in many fruits and vegetables and has been shown to have the potential to regulate lipid metabolism. However, the detailed mechanism by which it affects the browning of white adipose tissue remains unclear. In the present study, we sought to determine how KPF induces adipocytes to undergo a browning transformation by establishing a primary adipocyte model and an obese mouse model. Our results showed that KPF-treated mice were rescued from diet-induced obesity, glucose tolerance and insulin resistance, associated with increased expression of adaptive thermogenesis-related proteins. KPF-promoted white adipose browning correlated with the AMPK/SIRT1/PGC-1α pathway, as the use of an AMPK inhibitor in preadipocytes partially reversed the observed browning phenotype of KPF-treated cells. Taken together, these data suggest that KPF promotes browning of white adipose tissue through activation of the AMPK/SIRT1/PGC-1α pathway. This study demonstrates that KPF is a promising natural product for the treatment of obesity by promoting white fat browning.